The written body Ethnographic inquiries about the relationship between the body, violence and writing in documents from the Córdoba morgue in 1975 - Rios, Lucia (Facultad de Filosofía y Humanidades. Museo de Antropología, 2024)
This article arises from an ethnographic investigation into the corpses of people murdered for political reasons in the 70s in Córdoba, focusing on the description of the records of the morgues to admit/discharge the corpses, referencing the formulas used in the documents of the morgue on corpses sent during the repressive process in the province of Córdoba. The object will be to investigate the treatment produced by a bureaucracy such as the morgue in the writing related to the death of people murdered in the context of repression. Focusing on this point, I am interested in showing how this treatment was “translated” in the documents prepared by morgueros in Córdoba, in 1975, maintaining an articulation between body, violence and writing in the configuration of a written body, configured from the writing whose trace remains in the documents. Writing produced by third parties who can omit, modify qualities about that written body which is, in turn, a narrated body, crossed by language (Das, 2016) and by violence.